Faunal Introductions to the Balearic Islands in the Early 1st Millennium Cal BC. Issue 5 (29th August 2017) - Ramis, Damià; Anglada, Montserrat; Ferrer, Antoni; Plantalamor, Lluís; Van Strydonck, Mark
Abstract: Only domestic mammals (sheep, goat, cattle, pig, and dog) and two rodent species constituted the faunal package introduced to the Balearic Islands by the early settlers in the 3rd millennium cal BC. Later animal introductions in the archipelago were thought to occur by the end of the 1st millennium cal BC due to contacts with Punic merchants or, more than likely, to the Roman conquest of the islands. Recently, several faunal remains belonging to different vertebrates (red deer, chicken, and rabbit) were found in the Talayotic site of Cornia Nou (Minorca), in contexts that date to the early 1st millennium cal BC. A series of radiocarbon ( 14 C) dates was made directly on samples of small species to exclude the possibility of infiltration into lower layers. The obtained results show that chicken and rabbit were already present on Minorca in the early 1st millennium cal BC. Chicken is recorded in Phoenician colonies in south Iberia as early as the 8th century cal BC. Rabbit, on the other hand, is indigenous to the Iberian Peninsula. These new faunal introductions recorded in Minorca could be related to the Late Bronze and Phoenician maritime activity.